Application of a new peroral anticoagulants in treatment and prophylaxis of thromboembolic complications - V. М. Меretskyi; І. V. Меretska (Клінічна хірургія)
Application of a new peroral anticoagulants in treatment and prophylaxis of thromboembolic complications